Циклическая стабильность сверхэластичности в состаренных монокристаллах Ni50,7Ti49,3 с модифицированной поверхностью - Фаткуллин, Илья Дмитриевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
As a result of the studies, it was found that the surface film (~420 nm) consisting of an oxide layer and a Ni-rich layer has a weak effect on the B2-R-B19' martensitic transformation temperatures and superelasticity in aged single crystals Ni50.7Ti49.3, oriented along the [001]B2-direction. There is a high cyclic stability of superelasticity in compression, in contrast to in tension. The oxide layer does not affect the parameters of the superelasticity curves and their cyclic stability in compression. The cracking of the surface oxide layer was not found during fatigue tests in compression.